2020
DOI: 10.15244/pjoes/110447
|View full text |Cite
|
Sign up to set email alerts
|

Water Body Detection Analysis Using NDWI Indices Derived from Landsat-8 OLI

Abstract: Water is the most important resource for sustaining life since it keeps the whole ecosystem alive and shapes human civilization [1,2]. Water resource management will be the most important issue in the future as it is today, especially for arid and semi-arid regions [3]. Due to the increasing population and consequent increase in food requirements, global warming and climate change, precision water resources management is of much greater importance -especially in the organization of agricultural irrigation acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 98 publications
(35 citation statements)
references
References 15 publications
0
29
0
6
Order By: Relevance
“…Figure 4B shows the stretching of positive pixel values of 0.70 to 0.95; the stretched raster indicated that areas with shallow waters tend to disappear from the raster and areas with deeper waters are revealed. Consequently, evaluating a signal of potential relative depth may be possible; deep portions of the stream could be associated with the highest pixel values and shallower areas with lower pixel values (Ozelkan 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Figure 4B shows the stretching of positive pixel values of 0.70 to 0.95; the stretched raster indicated that areas with shallow waters tend to disappear from the raster and areas with deeper waters are revealed. Consequently, evaluating a signal of potential relative depth may be possible; deep portions of the stream could be associated with the highest pixel values and shallower areas with lower pixel values (Ozelkan 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Yakın kızılötesi (YKÖ) yerine kısa dalga kızılötesi bölgesi (KDKÖ) kullanılarak oluşturulan modifiye NDWI (MNDWI) ise suyun, elektromanyetik spektrumun yeşil bölgesindeki yüksek yansıtım ile kısa dalga kızılötesi (KDKÖ) bölgesindeki düşük yansıtımı arasındaki zıtlığı kullanır (2). MNDWI da -1 ile 1 arasında değer alır, genel olarak pozitif değerleri suyu ifade eder ve aşağıdaki şekilde formülize edilir [11,31,32,37]. MNDWI = (Yeşil Bölge − KDKÖ) / (Yeşil Bölge + KDKÖ) (2) Çalışma sahasının özelliklerine göre değişiklik gösterse de sulak alanların diğer arazi kullanımı/örtüsü sınıflarından ayırt edilmesinde MNDWI'ın diğer indislere göre daha başarılı olduğu birçok çalışmada ispatlanmıştır [1,6,11,37,46]…”
Section: çAlışma Alanıunclassified
“…Yakın kızılötesi (YKÖ) yerine kısa dalga kızılötesi bölgesi (KDKÖ) kullanılarak oluşturulan modifiye NDWI (MNDWI) ise suyun, elektromanyetik spektrumun yeşil bölgesindeki yüksek yansıtım ile kısa dalga kızılötesi (KDKÖ) bölgesindeki düşük yansıtımı arasındaki zıtlığı kullanır (2). MNDWI da -1 ile 1 arasında değer alır, genel olarak pozitif değerleri suyu ifade eder ve aşağıdaki şekilde formülize edilir [11,31,32,37].…”
Section: çAlışma Alanıunclassified
See 1 more Smart Citation
“…During the acquisition of spatial data using geodetic methods, these models are created using a series of measured point elements that are determined through a bound (connected to the geodetic framework), or a locally selected coordinate system with the coordinates x, y, z. Bak et al claim that there are several surveying methods used in mine surveying activities which enable the mining surveyor to get a fair idea of the studied mining works [12][13][14]. The current state of science and technology is the basis for using these surveying procedures, methods and tools that result from an effort to rationalize measurement procedures by using the latest equipment and facilities [15][16][17][18][19]. Jaafar et al say that the big problem of mine surveying activity has long been the lack of legislation across the EU; it is outdated and not adapted to the new trends and possibilities of our time and it also does not reflect the position of Europe as historically an important mining area [20].…”
Section: Introductionmentioning
confidence: 99%